Effect of sodium bicarbonate and varying concentrations of sodium chloride in brine on the liquid retention of fish (Pollachius virens L.) muscle. (12th May 2015) - Åsli, Magnus; Ofstad, Ragni; Böcker, Ulrike; Jessen, Flemming; Einen, Olai; Mørkøre, Turid
Abstract: BACKGROUND: Negative health effects associated with excessive sodium (Na) intake have increased the demand for tasty low‐Na products (<2% NaCl) rather than traditional heavily salted fish products (∼20% NaCl). This study investigates the causes of improved yield and liquid retention of fish muscle brined with a combination of salt (NaCl) and sodium bicarbonate (NaHCO3 ). RESULTS: Water characteristics and microstructure of saithe ( Pollachius virens L.) muscle brined in solutions of NaCl and NaHCO3 or NaCl alone were compared using low‐field nuclear magnetic resonance (LF‐NMR) T 2 relaxometry, microscopy, salt content, liquid retention and colorimetric measurements. Saithe muscle was brined for 92 h in 0, 30, 60, 120 or 240 g kg −1 NaCl or the respective solutions with added 7.5 g kg −1 NaHCO3 . NaHCO3 inclusion improved the yield in solutions ranging from 0 to 120 g kg −1 NaCl, with the most pronounced effect being observed at 30 g kg −1 NaCl. The changes in yield were reflected in water mobility, with significantly shorter T 2 relaxation times in all corresponding brine concentrations. Salt‐dependent microstructural changes were revealed by light microscopy, where NaHCO3 supplementation resulted in greater intracellular space at 30 and 60 g kg −1 NaCl. CONCLUSION: Sodium bicarbonate addition to low‐salt solutions can improve yield and flesh quality of fish muscle owing to altered water mobility and wider space between the muscle cells. © 2015 Society of Chemical Industry